2019
DOI: 10.1021/acschemneuro.9b00646
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Recruitment of Conformationally Distinct Amyloid-β Oligomers by the Intrinsically Disordered Region of the Human Prion Protein

Abstract: Soluble oligomeric species of the amyloid-β (Aβ) peptide exhibit pronounced neurotoxic effects in Alzheimer’s disease. Recent studies have indicated that the prion protein (PrP) is one of the cell-surface receptors, so-called a bad receptor, of Aβ oligomers that mediates downstream cellular toxicity. A rational classification of Aβ oligomers on the basis of conformation indicates that there are two distinct types of oligomers, namely, prefibrillar and fibrillar oligomers that are positive to A11 and OC conform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 62 publications
2
26
0
Order By: Relevance
“…Instead, the high degree of β-strand content indicates that Aβ oligos already contain Aβ monomer units that have at least in part the same secondary structure as in fibrils or protofibrils, but probably differ in tertiary structure. This phenomenon has already been observed in early stage Aβ oligomers (8,72) and is supported by the finding that huPrP-mediated toxicity depends partially on high-molecularweight fibrillar-like Aβ oligo (59,60). Assuming that the Aβ oligo preparation yielded a heterogeneous collection of fibril-like conformers in terms of secondary structure, of which most if not all were obviously elongation incompetent when trapped by adding huPrP, one would expect that the solid-state NMR resonances of Aβ oligo in complex with huPrP are the sum of the resonances of different fibril conformations together with resonances from Aβ units that experience different environments due to edge effects and/or huPrP interaction.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Instead, the high degree of β-strand content indicates that Aβ oligos already contain Aβ monomer units that have at least in part the same secondary structure as in fibrils or protofibrils, but probably differ in tertiary structure. This phenomenon has already been observed in early stage Aβ oligomers (8,72) and is supported by the finding that huPrP-mediated toxicity depends partially on high-molecularweight fibrillar-like Aβ oligo (59,60). Assuming that the Aβ oligo preparation yielded a heterogeneous collection of fibril-like conformers in terms of secondary structure, of which most if not all were obviously elongation incompetent when trapped by adding huPrP, one would expect that the solid-state NMR resonances of Aβ oligo in complex with huPrP are the sum of the resonances of different fibril conformations together with resonances from Aβ units that experience different environments due to edge effects and/or huPrP interaction.…”
Section: Discussionsupporting
confidence: 71%
“…Aside from the protective role of soluble huPrP in AD, membrane-anchored huPrP is mediating neurotoxicity of Aβ(1-42) oligo (19,24,25) via Fyn-kinase (26,27) or NMDA receptor pathways (57). Although Aβ(1-42) oligo toxicity is not solely dependent on huPrP (28-31), it has been shown that especially small Aβ(1-42) oligo (58) and high-molecular-weight Aβ(1-42) oligo (59,60) mediate toxicity by huPrP. To target this interaction efficient inhibitors might prevent Aβ(1-42) oligos ' detrimental effects.…”
Section: Discussionmentioning
confidence: 99%
“…To further reconfirm the spherical entities as amyloid oligomers, we probed the NM-Hsp104 aggregation reactions using A11 antibody that is specific for oligomers. 33,34,35 In the sample spotted after 7h from the commencement of the reaction, we detected a weak signal indicating the existence of a low fraction of oligomeric species in the presence of a low concentration of Hsp104 but not in the absence of Hsp104. This weak A11 activity in the presence of Hsp104 disappeared after 30h due to the conversion of all oligomeric species into matured fibrils (Figure 1g).…”
Section: Resultsmentioning
confidence: 85%
“…PrP 23-144 (Y145Stop), PrP 112-231, and single cysteine variants of full-length PrP (W31C and W99C) were used as described previously. 63,90 Recombinant full-length human α-Syn (1-140) plasmid cloned in vector pT7.7 was transformed in BL21(DE3)pLysS. 91 α-Syn (1-102) (N103Stop) and α-Syn (1-132) (Y133Stop) were created using the full-length α-Syn plasmid.…”
Section: Methodsmentioning
confidence: 99%
“…91 Recombinant prion protein constructs were overexpressed and purified using previously published protocols. 63,90 The purified proteins were refolded using the PD10 column in 14 mM MES buffer, pH 6.8. Recombinant α-Syn constructs except 103Stop were purified using the anion-exchange chromatography as described previously.…”
Section: Methodsmentioning
confidence: 99%